PENGEMBANGAN INSTRUMEN TES UNTUK MENGUKUR KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Labibah, Farah; Faizah, Siti; Mardhatillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of references for HOTS questions is considered an obstacle for teachers in developing HOTS-based questions. This study aims to produce test instrument development products to measure students' critical thinking skills in Pancasila Education subjects. This type of research is research and development (R&D) using the ADDIE method which consists of five stages namely analyze, design, development, implementation, and evaluation. The research instruments were a validation questionnaire and a critical thinking skills test. The types of data generated are quantitative data and qualitative data. The quantitative data in the form of the results of the validity of the test instrument products by experts reached an average score of 0.94 with very high validity criteria. While the qualitative data in this study are in the form of suggestions and input from experts, namely (1) Paying attention to the connection of question items with the real life of students and (2) Correcting the word “exclusion” so that it can be better understood by students. Then the empirical validity test was carried out by testing the test instrument on 3 fourth grade students of SDN Madulegi II to produce quantitative data in the form of an average score on each aspect of critical thinking ability based on the FRISCO framework. The results showed that the focus, inference, and situation aspects achieved an average score of 2.5 and the clarity aspect of 2.75 which was in the high category. Meanwhile, the other aspects, namely reason and overview, only reached the medium category with an average score of 2.25. Based on the results of the study, it can be concluded that the test instrument developed is able to measure students' critical thinking skills in Pancasila Education subjects.